QoS provisioning in OBS networks with an easy improvement to the Staged Reservation Scheme (SRS) - Abid, A.; Mellah, H.; Ewe, Hong Tat; Abbou, F. M. (IEEE, 2005)
The Internet traffic is exponentially increasing, and the IP's traditional "Best Effort" strategy is not efficient enough to support the current and future real-time and mission-critical applications. In this paper, a new technique is proposed for providing differentiated services to IP packets over an optical burst-switching (OBS) network. Based on the Staged Reservation Scheme (SRS), a new approach for assembling packets into data burst is presented. In this approach, packets with different QoS requirements are assembled into the same data burst. The packets are placed into the burst in a way that makes the low priority packets the first to be dropped compared to the higher priority packets, incase of contention. Furthermore, the proposed scheme is enhanced via a now control mechanism. Based on simulation results, it is shown that an adequate QoS level could be achieved with a simple and easy modification to the original SRS signaling protocol.